'I say high, you say low': the Beatles and cultural hierarchies in 1960s and 1970s Britain. Issue 3 (December 2020) - Collins, Marcus
Abstract: The debate over the cultural value of the Beatles was as vehement as it was significant in 1960s and early 1970s Britain. Lennon and McCartney's early compositions received some early critical plaudits, Sgt. Pepper sought to blur distinctions between high and low culture and the band members' side projects forged links with the avant garde. To accept the Beatles as artists, however, required critics to rethink how art was created, disseminated and evaluated and how it interacted with contemporary social, economic and technological change. This article makes extensive use of contemporary journalism, scholarship and fan literature, much of it unstudied, to demonstrate that the rethinking process was contested and protracted. No consensus emerged. Claims made for their artistry, which contributed to a wider discourse elevating 'rock' over 'pop', were countered by cultural conservatives who defended their own status as artists and intellectuals by exposing the Beatles as kitsch.